Genetic Modification of Mucor circinelloides for Canthaxanthin Production by Heterologous Expression of β-carotene Ketolase Gene - Naz, Tahira; Yang, Junhuan; Nosheen, Shaista; Sun, Caili; Nazir, Yusuf; Mohamed, Hassan; Fazili, Abu Bakr Ahmad; Ullah, Samee; Li, Shaoqi; Yang, Wu; Garre, Victoriano; Song, Yuanda (Frontiers in Nutrition, 2021)
Canthaxanthin is an orange-reddish xanthophyll with strong antioxidant activity and higher bioavailability than carotenes, primarily used in food, cosmetics, aquaculture, and pharmaceutical industries. The spiking market for natural canthaxanthin promoted researchers towards genetic engineering of heterologous hosts for canthaxanthin production. Mucor circinelloides is a dimorphic fungus that produces β-carotene as major carotenoid and considered as a model organism for carotenogenic studies. In this study, canthaxanthin producing M. circinelloides strain was developed by integrating the codon optimized β-carotene ketolase gene (bkt) of the Haematococcus pluvialis into the genome of the fungus under the control of strong promoter zrt1. Firstly, a basic plasmid was constructed to disrupt crgA gene, a negative regulator of carotene biosynthesis, resulted in substantial β-carotene production which served as the building block for canthaxanthin by further enzymatic reaction of the ketolase enzyme. The genetically engineered strain produced significant amount (576 ±28 µg/g) of canthaxanthin which is the highest amount reported in Mucor till date. Moreover, the cell dry weigh of recombinant strain was also determined, producing up to more than (9.0 g/L), after 96 h. The mRNA expression level of bkt in the overexpressing strain was analyzed by RT-qPCR, which increased by 5.3, 4.1 and 3 folds at 24, 48 and 72 h respectively, compared to control strain. The canthaxanthin producing M. circinelloides strain obtained in this study provided a basis for further improving the biotechnological production of canthaxanthin and suggested a useful approach for the construction of more valuable carotenoids such as astaxanthin.